Pengaruh Pembiayaan BUS Devisa, Pembiayaan Syariah LPEI, dan Penanaman Modal Asing (PMA) terhadap Ekspor Industri Pengolahan Nonmigas Indonesia - Dinda Siti Nur'ainiyyah; Ade Ali Nurdin; Fifi Afiyanti Tripuspitorini (Journal of Applied Islamic Economics and Finance, 2021)
This research aims to analyze the effect of Foreign Exchange Islamic Bank financing, LPEI sharia financing, and Foreign Direct Investment (FDI) either partially or simultaneously on the export of Indonesia’s non-oil and gas processing industries in the period of 2013 – 2020. This research is a quantitative study using purposive-sampling for its sampling method. The data used are in quantitative form and based on time series measurements. Data were collected by using documentation method of secondary data from five Foreign Exchange Islamic Bank, LPEI, BKPM, and BPS. The data analysis method used is multiple linear regression ordinary least square (OLS) using the program R Studio. The results show that simultaneously, all of the independent variables have an effect on the export of Indonesia’s non-oil and gas processing industries. Meanwhile partially, LPEI sharia financing and FDI have no significant effect. Foreign Exchange Islamic Bank financing partially has a positive and significant effect.